Peran Loyalitas Kerja dalam Memediasi Pengaruh Budaya Organisasi dan Pengembangan Karir Terhadap Kinerja Karyawan - Yuliana Kartika Sari; Anis Turmudhi (CV. Ulil Albab Corp, 2024)
The purpose of this research is to examine organizational culture and development which has an impact on employee performance, which can be mediated by work loyalty. This research uses path analysis with research that examines the relationship between elements of organizational culture, career development on work loyalty and employee performance. The sample in this study was all employees at veterinary clinics, animal salons and pet shops GSL Semarang who could provide relevant information regarding employee performance. Data collection was carried out by questionnaire using Google Form. Data analysis using the SPSS version 2.7 method which processed 52 respondent data. The research results show that there is a positive and significant influence on the relationship between organizational culture and employee performance. Meanwhile, the influence of career development on employee performance is not significant. There is a positive and significant influence on organizational culture on work loyalty. Meanwhile, the influence of career development on work loyalty has no effect. The results also show that work loyalty mediates the relationship between organizational culture and career development on employee performance and has no effect